2019
DOI: 10.20517/2574-1209.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the mechanical properties of the aortic wall

Abstract: Characterizing the physical properties of the aortic wall is essential to understanding the causes of cardiovascular diseases, such as aneurysms. Modelling compliant, anisotropic, multilayered tubes such as the aorta has proven to be a challenge. In vitro studies of the mechanical properties of arteries incorporate a variety of testing methods; however, the majority of these tests fail to replicate the complex, transmural loading conditions arising from pulsatile flow. These methods include typical tensile tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Little data on compression of vessels is reported, as vessels are usually loaded by intra‐luminal pressure for which the tensile modulus is of interest. [ 30,31 ] Compressive vessel investigations found in literature focus on blood supply during pregnancy, cardiopulmonary resuscitation or aortae calcification determination. One study reported on calcified porcine aortae up to compressive strains of 50%, [ 29 ] strains too low for hydrogel disintegration.…”
Section: Resultsmentioning
confidence: 99%
“…Little data on compression of vessels is reported, as vessels are usually loaded by intra‐luminal pressure for which the tensile modulus is of interest. [ 30,31 ] Compressive vessel investigations found in literature focus on blood supply during pregnancy, cardiopulmonary resuscitation or aortae calcification determination. One study reported on calcified porcine aortae up to compressive strains of 50%, [ 29 ] strains too low for hydrogel disintegration.…”
Section: Resultsmentioning
confidence: 99%
“…Aortic walls are usually composed of three layers, the intima, media and adventitia layers [24]. The tissue of each layer is comprised of networks of collagen fibers embedded in a ground matrix and can be regarded as fiber reinforced composites, of which the mechanical properties are anisotropic [25][26][27], similar to engineering fiber-reinforced composites [28][29][30][31][32]. Schriefl at al.…”
Section: Unified-fiber-distribution (Ufd) Hyperealstic Modelmentioning
confidence: 99%
“…This degradation affects the mechanical properties of the AAA wall, including its strength, and it varies significantly from patient to patient as well as within an AAA [ 5 ]. Because there is no current clinical test to non-invasively assess microscopic tissue composition, AAA wall properties continue to be elusive [ 95 ]. Attempts have, therefore, been made to correlate AAA wall properties, including wall strength, to non-invasive measurements such as metabolic activity (assessed by positron emission tomography scans, PET/CT) or blood biomarkers of tissue degradation activity, e.g., [ 94 , 96 ].…”
Section: Studies and Limitationsmentioning
confidence: 99%